Analysis of carbon substrates used by Listeria monocytogenes during growth in J774A.1 macrophages suggests a bipartite intracellular metabolism - Stephanie eGrubmüller; Kristina eSchauer; Werner eGoebel; Thilo M Fuchs; Wolfgang eEisenreich (Frontiers in Cellular and Infection Microbiology, 2014)
Intracellular bacterial pathogens (IBP) are dependent on various nutrients provided by the host cells. Different strategies may be therefore necessary to adapt the intracellular metabolism of IBPs to the host cells. The specific carbon sources, the catabolic pathways participating in their degradation, and the biosynthetic performances of IBPs are still poorly understood. In this report, we have exploited the technique of 13C-isotopologue profiling to further study the carbon metabolism of Listeria monocytogenes by using the EGDe wild-type strain and mutants (defective in the uptake and/or catabolism of various carbon compounds) replicating in J774A.1 macrophages. For this goal, the infected macrophages were cultivated in the presence of [1,2-13C2]glucose, [U-13C3]glycerol, [U-13C3]pyruvate, [U-13C3]lactate, or a mix of [U-13C]amino acids. GC/MS-based isotopologue profiling showed efficient utilization of amino acids, glucose 6-phosphate, glycerol, and (at a low extent) also of lactate but not of pyruvate by the IBPs. Most amino acids imported from the host cells were directly used for bacterial protein biosynthesis and hardly catabolized. However, Asp was de novo synthesized by the IBPs and not imported from the host cell. As expected, glycerol was catabolized via the ATP-generating lower part of the glycolytic pathway, but apparently not used for gluconeogenesis. The intermediates generated from glucose 6-phosphate in the upper part of the glycolytic pathway and the pentose phosphate shunt likely serve primarily for anabolic purposes (probably for the biosynthesis of cell wall components and nucleotides). This bipartite bacterial metabolism which involves at least two major carbon substrates - glycerol mainly for energy supply and glucose 6-phosphate mainly for indispensible anabolic performances - may put less nutritional stress on the infected host cells, thereby extending the lifespan of the host cells to the benefit of the IBPs.